2021
DOI: 10.1017/age.2020.24
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic Pricing of Rice Attributes, Market Sorting, and Gains from Quality Improvement in the Beninese Market

Abstract: Latent class analysis is applied to a hedonic price model to examine the presence of heterogeneity in consumer valuation of quality attributes in the Beninese rice market. Three classes of consumers are found in proportions of 5, 56, and 39 percent. We employ a partial equilibrium model and find modest gains in consumer surplus from an increase in head rice and reduction in chalkiness. The results provide evidence of market sorting, which should be taken into consideration in upgrading rice value chains. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Preference for parboiled rice has been observed in Benin (Naseem et al, 2013), and therefore, parboiling of rice using improved technology is seen as a viable means to increasing the competitiveness of domestic rice value chains (Akoa Etoa et al, 2016). Similarly, consumer preference for rice sold in urban markets to that sold in rural ones has been observed for two classes of consumers in the Beninese market (Ndindeng et al, 2021b). The results reveal negative implicit prices for impurities, amylose content, and imported rice.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Preference for parboiled rice has been observed in Benin (Naseem et al, 2013), and therefore, parboiling of rice using improved technology is seen as a viable means to increasing the competitiveness of domestic rice value chains (Akoa Etoa et al, 2016). Similarly, consumer preference for rice sold in urban markets to that sold in rural ones has been observed for two classes of consumers in the Beninese market (Ndindeng et al, 2021b). The results reveal negative implicit prices for impurities, amylose content, and imported rice.…”
Section: Resultsmentioning
confidence: 64%
“…Future reduction in amylose content in the Philippines was expected to yield a BCR of 9 and IRR of 29. Ndindeng et al (2021b) have found rather small gains in consumer surplus if there is an increase in head rice and a reduction in chalkiness. The hedonic price model in both studies is the consumer goods characteristics model (CGCM) of Ladd and Suvannunt (1976).…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Collaborations of the Japanese scientists with economists are also actively implemented and several joint articles have been published (e.g. Arouna et al 2021a, Arouna et al 2021b, Diagne et al 2013a, Diagne et al 2013b, Fiamohe et al 2018, Ndindeng et al 2021b.…”
Section: Attempts To Upgrade the Whole Rice Value-chain In The Past 1...mentioning
confidence: 99%